The rental [videorecording (DVD)] - Franco, Dave, 1985-; Brie, Alison; Ridler, Jovani; Huss, Toby, 1966-; Stevens, Dan, 1982- (Scream Factory, 2020)
Two couples on an oceanside getaway grow suspicious that the host of their seemingly perfect rental house may be spying on them. Before long, what should have been a celebratory weekend trip turns into something far more sinister, as well-kept secrets are exposed and the four old friends come to see each other in a whole new light..